Menjunjung Tinggi Multilateralisme: Kebijakan Luar Negeri Indonesia dalam Merespons Pandemi Covid-19 - Luerdi Luerdi; Azhari Setiawan (Jurnal Ilmiah Hubungan Internasional, 2022)
The 2019 Coronavirus disease or COVID-19 has apparently become a new global challenge. Not only did the pandemic drive all actors to make response, but it also affected the relations among them. That Indonesia raised multilateralism in the unprecedented situation while more unilateral or populist actions taken by a number of states encouraged this research. This paper attempts to explain Indonesia’s foreign policy in upholding multilateralism to respond to the COVID-19. Such response was intended to mitigate the impacts caused by the pandemic. This research applied holistic constructivism in understanding the determinants of Indonesia’s foreign policy by investigating both domestic and international cause. This research utilized the qualitative method with an explanatory analysis. The findings show that such Indonesia’s foreign policy was driven by its identity constructed by both indigenous norm of ‘Gotong Royong’ and global norm of ‘International Health Regulation’. The norm-laden or identity-based foreign policy was leading it to uphold multilateralism which was considered appropriate in order to coordinate, collaborate and cooperate with international communities. In addition, Indonesia maintained its trust on and support to the World Health Organization as the most leading actor in health governance championing fight against the pandemic. This paper argues that the norm factors do matter in Indonesia’s foreign policy in facing uncertainties in the vulnerable and interconnected world. Through the case studied, this paper suggests that looking at the domestic actor as well as the state in international system help provide a better understanding on the state behavior in international relations.